Postharvest quality of melon (Cucumis melo L.) by effect of iodinated chitosan complexes - Ortega-Ortiz, Hortensia; Soriano-Melgar, Lluvia de Abril Alexandra; Treviño-López, Eduardo Alfonso (Ecosistemas y Recursos Agropecuarios, 2023)
Iodine is an essential element for humans because its deficiency can affect human health by causing hypothyroidism, congenital anomalies, cretinism, cognitive function, among others. Traditionally, table salt has been used to prevent iodine deficiency disorders, but it increased the risk of cardiovascular diseases. For this reason, it is a necessary to implement new adequate, and healthy strategies for iodine supplementation. Iodinated chitosan complexes in fruits can be a good alternative to improve biofortification, in addition to increasing crop yield and quality. In the present work, the effects of KI and KIO3 salts, chitosan-KI complex (CS-KI), chitosan-KIO3 complex (CS-KIO3), chitosan as control and water as absolute control on melons fruits were evaluated, each treatment consisted of doses of 5 and 25 mg Kg-1 foliarly. The results show that the application of CS-I complexes positively modifies carotenoids content, increases vitamin C content, and maintained the total antioxidant capacity for 15 days after storage, indicating the conservation of the nutraceutical content of melon fruits.
Keywords: antioxidants; Biofortification; complexes; iodine; melon